In Vivo Pharmacological and Anti-inflammatory Evaluation of Xerophyte Plantago sempervirens Crantz - Farcaș, Anca D. (Oxid Med Cell Longev, 2019)
Known for centuries throughout the world, Plantago species have long been used as traditional herbal remedies for many diseases related to inflammatory conditions of the skin, respiratory and digestive tract, or even malignancy. This study is aimed first at investigating the in vitro antioxidant and regenerative effects of Plantago sempervirens Crantz hydroalcoholic extract followed by an in vivo experiment using a turpentine oil-induced inflammation model. The in vitro evaluation for antioxidant activity was performed using classical assays such as DPPH and TEAC scavenging assays but also EPR, and the total phenolic content was determined using the Folin-Ciocalteu reagent. The wound healing assay was performed on human cells (Human EA.hy926). Besides, the prooxidant activity was determined using a method which involves in situ free radical generation by laccase and the oxidation of haemoglobin. On turpentine oil-induced inflammation in rats, the in vivo effects of three doses of P. sempervirens extracts (100%, 50%, and 25%) were assessed by measuring oxidative stress (MDA, TOS, OSI, NO, CAT, and SOD) and inflammatory (CRP, WBC, and NEU) parameters. Having a rich polyphenolic content, the xerophyte P. sempervirens exhibited a strong in vitro antioxidant activity by scavenging radicals, enhancing cell regeneration, and reducing oxidative stress markers. Diluted P. sempervirens extract (25%) exhibited the best antioxidant, wound healing, and anti-inflammatory activity.